Global climate change issues, natural disasters and their impact on Indonesian children - Kurniawan Taufiq Kadafi; Dimas Dwi Saputro; Martinus M. Leman; Aslinar; Badai Buana Nasution; Dimas Tri Anantyo; Niken Wahyu Puspaningtyas; Fathy Zuandy Pohan; I Nyoman Arie Purwana; Muhammad Reza; Jaya Ariheryanto Effendy; Yogi Prawira; Piprim Basarah Yanuarso, (Pediatric Sciences Journal, 2022)
Climate change that contributes to the destruction of the earth is one of the impacts of human behavior. One example of damage to the earth due to human behavior is global warming. One of the effects of global warming is the melting of permafrost. Melting of glaciers due to global warming will result in an isostatic rebound phenomenon, where melting glaciers will cause the weight of the earth's crust to decrease and it is easy to move and bounce, resulting in the movement of earth faults and increased activity in the magma chamber (increased seismic activity). The big impact is the occurrence of natural disasters that not only occur in parts of the world where glaciers melt but in other parts of the world far from where glaciers melt. Natural disasters that can occur are earthquakes, volcanic eruptions, tsunamis, and landslides. Global warming will also have an impact on the emergence of disease outbreaks. Indonesia is the meeting place of three major tectonic plates in the world, namely the Eurasian plate, the Indo-Australian plate and the Pacific plate. In addition, Indonesia is also located in the Pacific ring of fire, making Indonesia an area with high volcanic activity and seismic activity. Climate change will increase the risk of disasters in Indonesia. The long experience of the Indonesian people in dealing with natural disasters that often occur should be used as a strategy to prevent and reduce the impact of disasters in the future.